2021
DOI: 10.1016/j.jpeds.2021.07.053
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki Disease and Pediatric Infectious Diseases During the Coronavirus Disease 2019 Pandemic

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 48 publications
(105 reference statements)
6
63
0
Order By: Relevance
“…However, in the acute phase of the outbreak, the number of patients over 5 years of age decreased, and the number of patients under 1 year of age increased. In addition, a study in Japan showed that during periods of social alienation, the decline in older KD children was greater than that in KD infants (<1 year), resulting in a significant difference in the proportion of infants between 2020 and 2017–2019 ( 27 ), which was consistent with our results. This also indicates that the incidence of Kawasaki disease is closely related to infection.…”
Section: Discussionsupporting
confidence: 91%
“…However, in the acute phase of the outbreak, the number of patients over 5 years of age decreased, and the number of patients under 1 year of age increased. In addition, a study in Japan showed that during periods of social alienation, the decline in older KD children was greater than that in KD infants (<1 year), resulting in a significant difference in the proportion of infants between 2020 and 2017–2019 ( 27 ), which was consistent with our results. This also indicates that the incidence of Kawasaki disease is closely related to infection.…”
Section: Discussionsupporting
confidence: 91%
“…Of these, two multicenter studies reported reductions of 47.1% and 53%, respectively, and one nationwide study reported a reduction of 35%. 21 22 23 These studies compared data from 2020 to records from the last 3–5 years. However, they were all focused on the correlation between KD and infectious diseases, and lack a discussion of changes in the clinical features of KD.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Similar hypotheses have been proposed in previous studies. 22 23 After the first case of COVID-19 in Korea, a high number of people started wearing masks and refrained from going out even before the government officially declared that social distancing was necessary, 7 which led to a nationwide decrease in respiratory infections. 24 In addition, at our institution, there was an immediate decrease in emergency room visits for pediatric infectious diseases after the first case of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations